Humanismo romanista y paralelismo intercultural entre los anticuarios andaluces y el Inca Garcilaso - Pino-Díaz, Fermín Del (Pontificia Universidad Católica del Perú. Fondo Editorial, 2014)
This article examines the Andalusian stage in the life of the author of the Comentarios Reales, as the original context of its creation. This literary context involves both its discursive nature (description of a culturally sufficient scenario, in dialogue with the reader) and its nationalist legitimation (the claim of an identity within the Christian Commonwealth). Such legitimation receives its characteristic mark of Renaissance logic (so common to the European nationalist process, from the fourteenth to the nineteenth century), but, more specifically, as a particular process of legitimizing stigmatized societies. In that sense, Andalucía, full of conversos incorporated into the Christian world (in Jewish and morisco minorities who claimed the right of Christian affiliation, recognized above all in the Society of Jesus until 1593) offered an ideal model for revindicating the despised, pre-Christian America (the Incas).

El presente artículo propone considerar la etapa andaluza del autor de losComentarios Reales como su contexto original de creación. Este contexto literario involucra tanto su naturaleza discursiva (descripción de un escenario culturalmente suficiente, en diálogo interpersonal con el lector) como su legitimación nacionalista (reclamación de identidad dentro de la Commonwealthc ristiana). Tal legitimación recibe su marca característica de la lógica renacentista (tan común al proceso nacionalista europeo, desde el siglo XIV al XIX), pero se matiza como un proceso particular de legitimación de sociedades estigmatizadas. En ese sentido, la Andalucía llena de conversos incorporados al universo cristiano (en minorías judías y moriscas que reclamaban el derecho a su pertenencia cristiana, reconocido excepcionalmente en la Compañía de Jesús hasta 1593) ofrecía un modelo reivindicativo idóneo para la América precristiana menospreciada (los incas).
Keywords: Historia; https://purl.org/pe-repo/ocde/ford#6.01.01